Perancangan Sistem Perencanaan Kegiatan Banyuwangi Festival Menggunakan Odoo Modul Event Dengan Metode Rapid Application Development - Pua Note, Faizal Ghiffary; Ramadani, Luthfi (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2023)
The tourism sector holds a pivotal role in Indonesia's economic landscape, particularly in Banyuwangi, where substantial growth has been witnessed. The Banyuwangi Festival, orchestrated annually by the Banyuwangi Regency Government through the Department of Culture and Tourism, stands as a flagship program contributing significantly to the upswing in tourist visits. Despite its prominence, the planning process for the Banyuwangi Festival involves multiple stakeholders, necessitating seamless coordination for comprehensive preparation. Unfortunately, the current reliance on spreadsheet tools diminishes the effectiveness of this process. Consequently, there is a pressing need for an advanced system to proficiently oversee the intricate planning of Banyuwangi Festival events. This research undertakes the ambitious task of conceptualizing and designing an Enterprise Resource Planning (ERP) system to address these challenges. Leveraging Odoo ERP, with the event module serving as the primary component and the website module as an additional feature, the study adopts the Rapid Application Development (RAD) method. This method is chosen to align with the specific requirements of the Banyuwangi Regency Culture and Tourism Department, which serves as the central coordinator for the Banyuwangi Festival. The outcome of this research is a sophisticated ERP system meticulously crafted to streamline three crucial processes: the submission of event proposals by the public or external entities, the event registration process, and the scheduling of meetings. This comprehensive ERP solution is poised to significantly enhance the Culture and Tourism Department's ability to manage and optimize the intricate planning of Banyuwangi Festival events, ultimately leading to more efficient business processes.